Does right ventricle dysfunction represent cardiac frailty in critically ill trauma patients?. (January 2020) - Flaubert, Mark; Lauerman, Margaret H; Haase, Daniel; Fatima, Syeda; Galvagno, Samuel; Scalea, Thomas M; Stein, Deborah M; Murthi, Sarah
Introduction: Cardiac function includes left ventricle ejection fraction, right ventricle function, diastolic function, and multiple markers of cardiac outflow. Markers of cardiac function associated with mortality are unknown. The purpose of this study was to determine markers of cardiac function associated with mortality in the elderly which represent cardiac frailty and the relative importance of these many measurements of cardiac function when compared with each other. Methods: A retrospective review of patients who underwent focused rapid echocardiographic evaluations was performed from 2009 to 2014. Focused rapid echocardiographic evaluations are echocardiographic exams focusing on cardiac function rather than structure. Results: Overall, 513 trauma patients received focused rapid echocardiographic evaluations. In elderly patients, mortality increase of 33.9% was seen with left ventricle ejection fraction less than 30% (p = 0.05), 28.5% with moderate right ventricle dysfunction (p = 0.03), and 18.5% with velocity time integral less than 18 cm (p = 0.02). Any level of diastolic dysfunction, cardiac output of less than 4 l/min, and cardiac index less than 2.5 l/min/m 2 was not significantly associated with increased mortality in the elderly (not significant [NS] for all). In younger patients, a mortality increase of 68.1% was seen with grade 3–4 diastolic dysfunction (p<0.001) and 14.6% with velocity time integral less than 18 cm (p = 0.02), with right ventricle dysfunction, decreased left ventricle ejection fraction, cardiac output less than 4 l/min, and cardiac index less than 2.5 l/min/m 2 not associated with mortality (NS for all). In logistic regression for elderly patients, only moderate right ventricle dysfunction was associated with mortality (odds ratio 4.321, 95% confidence interval 1.451–12.866, p = 0.009). Conclusions: Markers of cardiac function associated with mortality vary with age. Right ventricle dysfunction may represent cardiac frailty, while diastolic dysfunction and left ventricle ejection fraction likely do not.